TERRESTRIAL HEAT FLOW IN ZONES OF ACTIVE FAULTS IN SOUTHERN EAST SIBERIA - Lysak S.V. (My University, 2002)
Active faults and faults reactivated in Cenozoic or, less often, Mesozoic time are considered in relation to regional heat flows in the Baikal Rift and its surroundings. Abnormal heat flow and manifestations of thermal activity (hot springs, Cenozoic volcanoes and flood basalts) are most often assoclated with faults. Thermal activity of faults, controlled by faulting mechanism and by the interplay of conductive and convective transport of deep heat, is the highest in strike-slip and normal faults and the lowest in thrusts. Geothermal parameters as indicators of regional tectonothermal activity can thus serve as a proxy in tectonic implications.